ผลตอบสนองทางพลศาสตร์ของคานช่วงเดียวเนื่องจากน้ำหนัก กระทำจากการเดินของมนุษย์ - จิตรค้ำคูณ, จักรกฤษณ์; แข็งขัน, เอกพงษ์; ศีตะปันย์, ปฤษทัศว์ (Naresuan University Engineering Journal, 2014)
งานวิจัยนี้มีจุดมุ่งหมายเพื่อศึกษาผลตอบสนองของคานช่วงเดียวที่เกิดจากพฤติกรรมการเดินของมนุษย์ ซึ่งมีระยะห่างระหว่างคนสองคนที่ไม่เท่ากัน โดยแบ่งลักษณะการเดินออกเป็น 3 กลุ่ม โดยมีเงื่อนไขที่แตกต่างกัน โดยกลุ่มที่ 1 มีการพ้องกันระหว่างระยะห่างการเดินกับระยะการก้าวเดิน และกลุ่มที่ 2 ซึ่งเป็นการพ้องกันระหว่างความถี่จากระยะการก้าวเดินกับความถี่ธรรมชาติของคานช่วงเดียว และกลุ่มที่ 3 เป็นกลุ่มซึ่งไม่มีการพ้องกันของตัวแปรใดๆ เลย จากผลวิจัยพบว่าผลตอบสนองที่มากที่สุดของคานช่วงเดียว เกิดขึ้นในกรณีที่ลักษณะการเดินมีระยะห่างการเดินกับระยะการก้าวเดินที่พ้องกัน การสั่นพ้องจากอัตราการเข้าถึงนี้เป็นอีกปัจจัยสำคัญที่ต้องพิจารณาในการออกแบบโครงสร้าง DYNAMIC RESPONSES OF A SIMPLE BEAM SUBJECTED TO PEDESTRIAN LOADING The purpose of this paper is to study the dynamic responses of a simple beam subjected to pedestrian loading due to a variable distance between two humans. Patterns of human walking investigated here were divided into three conditions. The first condition was walking distance between two humans in synchronized with walking footstep. The second condition was that frequency of step walking was equal to natural frequency. Last condition was the general case in which there was no relationship among any parameters. The results showed that the highest amplification of the response of the simple beam was observed when walking distance between two humans was equal to walking step. Therefore, resonance due to arrival rate is another significant factor in structural design.